2018
DOI: 10.1021/acssuschemeng.7b04823
|View full text |Cite
|
Sign up to set email alerts
|

Complete Column Trials for Water Refinement Using Titanium(IV) Phosphate Sorbents

Abstract: A titanium phosphate sorbent with linked active units (LTP) is synthesized. XRD, 31P MAS NMR, and TGA techniques are used to disclose the relation between the ion-exchange units of −HPO4 (crystalline α-TiP) and of −H2PO4 (amorphous TiP1) type. The reported kinetics data of TiP1 sorbent in batch mode have been reprocessed according to the nonlinear approach in order to explore further the sorption mechanism. It was found that the data could be well described by the pseudo-second-order model in the case of Ni2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The amounts of metal ions sorbed on TiP1 determined from the Thomas model ( q Th ) are in very good agreement with the ones calculated from the experimental data. Similar observations were reported for another TiP system, where the Thomas model was used to describe the sorption of nickel ions . The breakthrough curves of model mine water could not be fitted accurately using the Thomas approach (with the exception of copper) due to the competitive sorption phenomenon that is strongly pronounced when all metal ions are present in equal amounts and/or the sorption equilibrium is maintained.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…The amounts of metal ions sorbed on TiP1 determined from the Thomas model ( q Th ) are in very good agreement with the ones calculated from the experimental data. Similar observations were reported for another TiP system, where the Thomas model was used to describe the sorption of nickel ions . The breakthrough curves of model mine water could not be fitted accurately using the Thomas approach (with the exception of copper) due to the competitive sorption phenomenon that is strongly pronounced when all metal ions are present in equal amounts and/or the sorption equilibrium is maintained.…”
Section: Resultssupporting
confidence: 67%
“…For aluminum, the desorption volume is about 70 BV, which is higher than for the other metals. Another study has also shown that it is possible to use HCl as a desorption solution instead of HNO 3 . It is advisible to examine the possibilities of complexation between the acid and the metal to determine the most suitable desorption solution to utilize.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations